PENINGKATAN PRESTASI MATA PELAJARAN MATEMATIKA KELAS IVSEMESTER II DENGAN SUB POKOK BAHASAN -SOAL CERITA MELALUI STRATEGI PROBLEM SOLVING DI MI AL-MA'ARIF BULUPAYUNG KECAMATAN PATIMUAN - Hayati, Sri (As-Sibyan, 2018)
This research is based on the initial observation in the form of a pre test for mathematics subjects with basic competencies that students must possess that is able to solve everyday problems involving mixed calculations. From the results of the pre-test, the average grade IV students only reached 63, even though the KKM determined was 70. Based on the initial data, the researchers carried out classroom action research with the following problem formulation: "Is it through Method Problem Solving Learning Achievement Subjects Mathematics Sub-Subjects of the Question The story involving mixed counting operations at MI Al-Ma'arif Bulupayung Patimuan District, Cilacap Regency can be improved? ". to find out the improvement of students' learning achievement in Mathematics Study Sub Subjects of Story Problems involving mixed counting operations. The research was conducted through a review process consisting of planning, implementation, observation, and reflection. From the results of the research conducted, it can be concluded that the use of problem solving strategies can increase the activity of students in learning, from 61% at the 4th Meeting of the Cycle I to 86% at the 4th Cycle II Meeting. The use of problem solving methods in learning mixed matter questions is able to provide a greater level of understanding of the material. In Cycle I the evaluation rate only reached 64.1%. Then with more understanding students' activities increased in Cycle II whichreached 86.07%.